THE RELATIONSHIP BETWEEN SELF-EFFICIENCY AND ADOLESCENT ACADEMIC ANXIETY - Diana Febi (Study Program Guidance and Counseling, Univesitas Pendidik, 2023)
Abstract: Efikasi diri is a person's inner belief in his own ability to organize and take action in order to achieve the results he wants. This research is motivated by the low efikasi diri of students, as well as the appearance of behavior that shows a tendency towards academic anxiety. This study aims to determine the relationship between efikasi diri and the level of academic anxiety in class VIII students of SMPN 1 Singaparna in the 2022/2023 academic year. This research was conducted using a quantitative approach and correlational methods. The population is 93 students, all members of the population are used as research samples so that generalizations with very small errors. The research data was obtained from the results of the distribution of instruments consisting of two variables, namely efikasi diri and academic anxiety which were distributed through the Google form. The results showed that (1) students' academic efikasi diri was in the medium category, namely 118 students (2) academic anxiety was in the moderate category, namely 111 students (3) the correlation category in this study was -0.524 with a significance level of 0.000 ( p0.05) indicates a fairly strong correlation in a negative direction, which means that the higher the level of efikasi diri, the higher the academic anxiety. Conversely, the lower the efikasi diri, the higher academic anxiety tends to be. Keywords: Seld Efficacy, Academic Anxiety, Correlational Study